Sulfur Degassing From Steam‐Heated Crater Lakes: El Chichón (Chiapas, Mexico) and Víti (Iceland). Issue 15 (9th August 2018) - Hasselle, N.; Rouwet, D.; Aiuppa, A.; Jácome‐Paz, M. P.; Pfeffer, M.; Taran, Y.; Campion, R.; Bitetto, M.; Giudice, G.; Bergsson, B.
Abstract: The composition of the gases released by El Chichón (Chiapas, Mexico) and Víti (Askja volcano, Iceland) volcanic lakes is examined by Multi‐GAS for the first time. Our results demonstrate that H2 S and SO2 are degassed by these pH 2–3 lakes. We find higher CO2 /H2 S and H2 /H2 S ratios in the lakes' emissions (31–5, 685 and 0.6–35, respectively) than in the fumarolic gases feeding the lakes (13–33 and 0.08–0.5, respectively), evidencing that only a fraction (0.2–5.4% at El Chichón) of the H2 S(g) contributed by the subaquatic fumaroles ultimately reaches the atmosphere. At El Chichón, we estimate a H2 S output from the crater lake of 0.02–0.06 t/day. Curiously, SO2 is also detected at trace levels in the gases released from both lakes (0.003–0.3 ppmv). We propose that H2 S supplied into the lakes initiates a series of complex oxidation reactions, having sulfite as an intermediate product, and ultimately leading to SO2 production and degassing. Plain Language Summary: Volcanic lakes are the site of some of the most unpredictable, and therefore dangerous, volcanic eruptions in nature. Their activity is driven by a feeding volcanic gas phase supplied by the underlying hydrothermal/magmatic system. These volatile species, entering the lake bottom, are absorbed into lake water at different rates/degrees depending on their water solubilities and the lake physical and chemical characteristics. Hyperacidic crater lakes (pH <1) are degassing SO2, a gas that was earlier believed to be totally dissolved into the water. In this study, we investigate for the first time the presence of reactive S gases (SO2 and H2 S) in the plumes of less acidic (pH 2–3) lakes El Chichón (Mexico) and Víti (Iceland). Our results demonstrate that H2 S, coming from the sublimnic hydrothermal systems is only partially dissolved and oxidized by the lake water. In addition, we discover trace amount of SO2 coming off both lakes. We propose that SO2 is produced into the lake by H2 S oxidation, with dissolved sulfite as an intermediate product. Our results thus open new piece of knowledge to our understanding and monitoring the activity of restless volcanic lakes. Key Points: H2 S dissolution and oxidation is inefficient in pH 2–3 lakes Sulfur degassing through pH 2–3 lakes is a kinetically driven process SO2 degassed from pH 2–3 lakes originates from H2 S oxidation with sulfites as transient species